2020
DOI: 10.1002/aenm.201903995
|View full text |Cite
|
Sign up to set email alerts
|

All‐Hydrocarbon MEA for PEM Water Electrolysis Combining Low Hydrogen Crossover and High Efficiency

Abstract: Hydrocarbon ionomers bear the potential to significantly lower the material cost and increase the efficiency of proton‐exchange membrane water electrolyzers (PEMWE). However, no fully hydrocarbon membrane electrode assembly (MEA) with a performance comparable to Nafion‐MEAs has been reported. PEMWE‐MEAs are presented comprising sPPS as membrane and electrode binder reaching 3.5 A cm−2 at 1.8 V and thus clearly outperforming state‐of‐the‐art Nafion‐MEAs (N115 as membrane, 1.5 A cm−2 at 1.8 V) due to a significa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
128
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 106 publications
(143 citation statements)
references
References 41 publications
7
128
1
Order By: Relevance
“…The relatively low free volume fraction observed in hydrocarbon‐based ionomers, particularly QA‐PPO, can contribute to the lower gas permeability and higher water uptake observed in these ionomers than perfluorinated ones in fuel cells and electrolyzers. [ 9,35 ]…”
Section: Discussionmentioning
confidence: 99%
“…The relatively low free volume fraction observed in hydrocarbon‐based ionomers, particularly QA‐PPO, can contribute to the lower gas permeability and higher water uptake observed in these ionomers than perfluorinated ones in fuel cells and electrolyzers. [ 9,35 ]…”
Section: Discussionmentioning
confidence: 99%
“…The spray coating procedure was adapted from Klose et al, 6 where details can be found. An ultrasonic spray coater (SNR 300, Sonocell) was used with a 60 kHz ultrasonic nozzle (Sonaer NS60K Atomizer) set to 90% power.…”
Section: Ccm Fabricationmentioning
confidence: 99%
“…4 Many emerging AEMs are based on uorine-free, hydrocarbon polymers with the potential advantage of lower synthesis cost compared to incumbent uorinebased membrane chemistry. 5 Some hydrocarbon PEM and AEM membranes (such as sulfonated poly(phenylene sulfone), sPPS 6 or Tokuyama 201 7 ) have shown a promising reduction of the gas crossover compared to the standard uorine-containing PEM (e.g. Naon) or alkaline electrolysis diaphragms.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…As alternative, sulfonated poly(phenylene sulfone) (sPPS) combines high proton conductivity with low gas crossover can be used. It has been reported that the performance of the sPPS-MEAs is substantially better than that of Nafion N115-MEAs (3.5 A•cm −2 vs 1.5 A•cm −2 at 1.8 V) with the same catalyst loading and comparable membrane thickness [170].…”
Section: Proton Exchange Membrane Electrolysis Cellmentioning
confidence: 96%